Amplified Spontaneous Emission of DCM Dye in PMMA Polymer Using Copper Metal Disks Mold - Al-Wattar, Abbas J. (Iraqi Journal of Physics, 2010)
The effect of irradiation and exposure time of laser light on the fluorescence emission of DCM dye in PMMA polymer contained in the composition mold using different metals have been investigated. It was found that the fluorescence intensity decreases as the exposure time increases and then reaches stabilization at long times. The effect of the incident laser power on fluorescence intensity of DCM dye in PMMA polymer at 10-3 M and 20% mixing ratio, using copper disks of composition molds, has been studied too. It was observed that there is an upward knick in the curve at laser intensity of 19.2 W/cm2, which may be associated with the threshold for amplified spontaneous emission (ASE) or laser action. And at intensity higher than about 88.8 W/cm2 nearly saturation is reached